2018
DOI: 10.29312/remexca.v9i7.550
|View full text |Cite
|
Sign up to set email alerts
|

Distribución geográfica potencial de papaya silvestre cultivada en México

Abstract: Las poblaciones silvestres de papaya (Carica papaya L.) integran un recurso biológico para el mejoramiento genético de la especie. La predicción de la distribución geográfica de las poblaciones silvestres y cultivadas es una herramienta útil para determinar sitios de colecta para su uso y conservación. Con el objetivo de estimar la distribución potencial de papaya en México, se elaboró una base de datos con información de geo-referenciación de individuos de papaya silvestre y cultivados, posteriormente se apli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…The Bioclim and Maxent statistical models enable the estimation of the geographical spatial distribution of wild species such as Jefea genus (Asteraceae) [ 43 ], Agave potatorum [ 44 ], Prosopis flexuosa [ 45 ], Vanilla planifolia [ 46 ], and Carica papaya [ 47 ]. However, the Maxent model has so far proved the most reliable for the analysis of the spatial distribution of a particular species because it does not take sampling bias into account.…”
Section: Study Areamentioning
confidence: 99%
“…The Bioclim and Maxent statistical models enable the estimation of the geographical spatial distribution of wild species such as Jefea genus (Asteraceae) [ 43 ], Agave potatorum [ 44 ], Prosopis flexuosa [ 45 ], Vanilla planifolia [ 46 ], and Carica papaya [ 47 ]. However, the Maxent model has so far proved the most reliable for the analysis of the spatial distribution of a particular species because it does not take sampling bias into account.…”
Section: Study Areamentioning
confidence: 99%
“…Con respecto a altitud y temperatura, existe una relación entre estas dos variables, ya que se obtuvo un valor de correlación negativo (t_max: r = -0.94, P ≤ 0.01; t_min: r = -0.97, P ≤ 0.01; t_mean: r = -0.99, P ≤ 0.01), por lo que a mayor altitud la temperatura decrece, lo que influye en la distribución de estas especies. En la distribución gráfica C. moschata y C. argyrosperma se ubicaron en el extremo positivo, las cuales prosperan en bajas altitudes y altas temperaturas; mientras que, en el extremo negativo se ubicaron las especies C. pepo y C. ficifolia, las cuales prosperan en las mayores altitudes y bajas temperaturas; al respecto, Espinosa et al (2018) encontraron resultados similares en la influencia de estos factores sobre la distribución de tipos de papaya (Carica papaya L.) silvestres y cultivados.…”
Section: Distribución Ecofisiográficaunclassified
“…In this context, several authors have reported the use of Bioclim and Maxent statistical models allowing the estimation of the geographical spatial distribution of wild species such as Jefea genus (Asteraceae) [22], Agave potatorum [23], Prosopis exuosa [24], Vanilla planifolia [25], and Carica papaya [26]. However, Maxent model is so far the most con dent for the analysis of the spatial distribution of a particular species because it does not take into account sampling bias.…”
Section: Introductionmentioning
confidence: 99%